RFID enabled safer cards for new gerneration ATM machines - Uma, S; Bhuvanya, R; Vijayalakshmi, K; Suresh, A (International Journal of Engineering and Technology, 2018)
The newer generation of ATM card is introduced for the current ATM machine. Instead of the ATM card, machine can be operated through the RFID tags. These RFID tags put an end to the usage of many number of ATM cards and provides a facility to integrate it into a single card named RFID Safer cards. When the safer card is inserted in the ATM machine the reader unit present in the machine, then the information about the card holder will be sent to the server. Information related to the user such as their account details, photo will be fetched from the server. Meanwhile the camera embedded in the machine will capture the image of the user and it will be compared with the image stored in the server. Hence the enhancement of security will be benefited when compared to the current ATM machine since it offers both the password and biometric capacity. If the particular image matches with the database it requests for the pin number and the transaction processing will be initiated. Otherwise the transaction will be aborted. When the user’s image matches with the database the system generated OTP will be sent to the user’s mobile. Then the user has to enter the obtained OTP to continue the banking process. Thus by using this system ATM card usage will be completely eliminated and it can be done by the RFID safer card. System malfunction can also be avoided which will make our transaction more secure.